THE CORRELATION BETWEEN LISTENING COMPREHENSION AND VOCABULARY ACHIEVEMENT OF THE ELEVENTH GRADE STUDENTS OF SMA LENTERA HARAPAN TORAJA - Gunawan S.Pd (UKI TORAJA, 2016)
The objective of the research was found the significant correlation between listeningcomprehension and vocabulary achievement of eleventh grade students of SMALentera Harapan Toraja. It was expected that result of the research that can gave usefulcontribution to English teaching, especially for English teachers, senior high schoolstudents and the readers about correlation between listening comprehension andvocabulary achievement. In this research, the writer used quantitative descriptivemethod. The population ofthis research was the eleventh grade students of SMALentera Harapan Toraja academic year 2015/2016. The number of population was 100students. Its consist of four classes. The writer took 20 students as sample. Theyselected by using random sampling which choose five students for every class. Theinstrument used to took the data was written test. It was used to find out the studentscomprehension in listening and to find out the students achievement in vocabulary.Based on the result above, the researcher analyze the relationship used Pearson’sProduct Moment Formula to correlate both listening comprehension (variable x) andvocabulary achievement (variable y). The result shows that is 0.561 andis 0.444. And is 2.875 and is 2.101. It means that the alternativehypothesis ( ) is accepted and the null hypothesis ( ) is rejected because r valuegreater than r table and t count greater than t table. The result can be concluded thatthere is positive and significant correlation between listening comprehension andvocabulary achievement of the eleventh grade students of SMA Lentera HarapanToraja.